Human Resource Management Strategies in Achieving Competitive Advantage in Business Administration - Agustian, Kresnawidiansyah; Pohan, Aryanda; Zen, Agustian; Wiwin, Wiwin; Malik, Aulia Januar (ADMAN: Journal of Contemporary Administration and Management, 2023)
Human Resource Management (HRM) is a very important aspect in the modern business world. Companies that manage their people effectively tend to have a greater competitive advantage over their competitors. This is due to the fact that HR is one of the most important assets in an organisation, and the ability to optimise HR potential, productivity and commitment will have a significant positive impact on company performance. This research aims to examine HR management strategies in achieving competitive advantage in business administration. This research uses a qualitative method of descriptive analysis to explore an in-depth understanding of the topic. This method allows researchers to explain in detail the characteristics, context, and factors related to the research topic. In this case, data was obtained from Google Scholar with a time span from 1996 to 2023. The results of this study show that effective HR management strategies are key to achieving and maintaining a competitive advantage in business administration. By prioritising aspects such as quality recruitment, employee development, motivation, efficient performance management, progressive corporate culture, responsiveness to change, and technology utilisation, companies can achieve better results in the face of intense business competition.